A modern view of the problem of constipation - Konstantin A. Shemerovskii; Raisa K. Kantemirova; Pavel V. Seliverstov (Лечащий Врач)
Background. PA new chronomedical approach to the classification of one of the most common syndromes in modern medicine, the constipation syndrome, is presented. According to Robert Hegglin "сonstipation is the absence of defecation for 24 hours". In contrast to the previously accepted "Roman Criteria of Constipation" (Rome IV), 2016, which recommended doctors to focus only on the frequency of defecation less than 3 times a week, a more reasonable chronophysiological approach to the criteria of this syndrome is presented. There are 2 more earliest stages of constipation that have not been diagnosed before. The first stage of constipation (mild) is with a frequency of defecation 5-6 times a week. The second stage of constipation (moderate) is with a frequency of defecation 3-4 times a week. The frequency of defecation, presented in the Roman criteria for constipation (less than three times a week), in the modern classification of constipation is presented as the third (severe) stage – with a frequency of defecation 1-2 times a week.Conclusions. It has been proven that the therapy of patients suffering from constipation is more effective at diagnosing the first and second stages of this syndrome than at the third stage of constipation. The presence of three stages of constipation is confirmed by a progressive (from stage I to stage III) deterioration in the quality of life, an increasing level of anxiety and depression, and an increase in the intake of laxatives from the first to the third stage of constipation. Examples of effective therapy of patients with constipation with the psyllium are presented.